ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SIKAP IBU DALAM PEMBERIAN MP-ASI DINI DI WILAYAH KERJA PUSKESMAS PERDAGANGAN KECAMATAN BANDAR KABUPATEN SIMALUNGUN TAHUN 2020 - erna manik (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
Mother's Milk (ASI) is the perfect substance for baby's growth and can accelerate the development of baby's weight. Complementary Food for Mother's Milk (MP-ASI) is food or drink that contains nutrients that are given to infants / children to meet nutritional needs. Appropriate complementary feeding is greatly influenced by the behavior of mothers who have babies. However, there are still many mothers who provide complementary foods for less than 6 months which can have a negative impact on the health of the baby. Many factors are related to early breastfeeding by the mother. These factors include knowledge, health and occupation of the mother, MP-ASI advertisements, health workers, cultural and socioeconomic. In order for the organizer's health efforts to be optimal, the Puskesmas must carry out a good assessment. This study aims to determine how mothers' attitudes towards early breastfeeding in the area of ​​Puskesmas Commerce in Bandar subdistrict, Simalungun Regency in 2020. This study is a survey with a cross-sectional research design. Sampling is done by using perposive sampling technique. The total sample in this study were 76 respondents. Data were analyzed by Chi Square test with α 0.05. The results of the study with bivariate analysis showed that there were influences between factors related to mother's attitudes namely education with p value (0.011) <α 0.05, occupation with p value (0.023) <α 0.05, husband support with p value ( 0.011) <α 0.05, and breastfeeding culture with a value of p (0.005) <α 0.05 in the provision of early breastfeeding MP in trade health centers in 2020. For the Simalungun District Health Office in order to provide counseling to the community especially to post partum mothers to always give exclusive breastfeeding to her baby until the age of 6 months without providing additional food such as formula milk, tea water, rice porridge and so forth. For trade Puskesmas so that Puskesmas employees can always provide the best service by providing information about early MP-ASI, how to give, due to giving MP-ASI too early to the mother so that the mother's insight becomes wider and her knowledge will be better. Keywords: Mother's Attitude, Giving MP-ASI, and Puskesmas.